2021
DOI: 10.1021/acsanm.1c00359
|View full text |Cite
|
Sign up to set email alerts
|

Few-Layer MoS2 Nanosheet/Carbon Nanotube Composite Films for Long-Lifetime Lithium Storage and Hydrogen Generation

Abstract: MoS 2 nanomaterials show excellent high theoretical performance in energy storage and hydrogen evolution reaction (HER), whereas they typically suffer from agglomeration and poor electrical conductivity. In this study, unique few-layer molybdenum disulfide nanosheet/carbon nanotube (MoS 2 /CNT) films are fabricated via an electrochemical exfoliation method. On the one hand, owing to the coupling effects of well-dispersed few-layer MoS 2 nanosheets and excellent conductive CNTs, these stateof-the-art films not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…They can also prevent Bi aggregation and buffer the large volume expansion during cycles. 24 The high-resolution TEM (HRTEM) image of the N,S-C@Bi/CNT (Fig. 1d) presents distinct lattice fringes, and the observed lattice distance of 0.32 nm corresponds to the (012) plane of hexagonal Bi crystals (JCPDS No.…”
Section: Resultsmentioning
confidence: 99%
“…They can also prevent Bi aggregation and buffer the large volume expansion during cycles. 24 The high-resolution TEM (HRTEM) image of the N,S-C@Bi/CNT (Fig. 1d) presents distinct lattice fringes, and the observed lattice distance of 0.32 nm corresponds to the (012) plane of hexagonal Bi crystals (JCPDS No.…”
Section: Resultsmentioning
confidence: 99%
“… 15 19 The addition of CNT can inhibit the agglomeration and accumulation of MoS 2 nanosheets, expand the layer spacing of MoS 2 , enhance the interlayer conductivity of MoS 2 , and make the redox reaction of MO 4+ go deeper into the interlayer of MoS 2 . 20 24 Although CNT can accelerate the electron transfer efficiency of MoS 2 –CNT composite electrodes, the weak interaction between them will significantly reduce the flexibility of composite electrodes and limit its development in flexible supercapacitor. Therefore, we can introduce a certain amount of nanocellulose into MoS 2 –CNT composite electrodes to improve their flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most convenient and effective ways to improve the electrochemical performance of composite electrodes by compounding with electrode materials that have complementary and synergistic effects on microstructure, crystal structure, electrical conductivity, and electrochemical performance. Among them, carbon nanotube (CNT) with ideal one-dimensional structure, excellent electrical conductivity, and large specific surface area is one of the more ideal carbon materials for the construction of MoS 2 composites. The addition of CNT can inhibit the agglomeration and accumulation of MoS 2 nanosheets, expand the layer spacing of MoS 2 , enhance the interlayer conductivity of MoS 2 , and make the redox reaction of MO 4+ go deeper into the interlayer of MoS 2 . Although CNT can accelerate the electron transfer efficiency of MoS 2 –CNT composite electrodes, the weak interaction between them will significantly reduce the flexibility of composite electrodes and limit its development in flexible supercapacitor. Therefore, we can introduce a certain amount of nanocellulose into MoS 2 –CNT composite electrodes to improve their flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have been intensively explored since 1991 because of their extraordinary features, including the high electrical conductivity, stability, and superior mechanical characteristics, as well as the alkali metal redox ability. Many researchers have validated the practical use of this material as catalysts, composites, and molecular wires, besides theoretical considerations on the potential as an inherently one-dimensional conducting polymer. However, many researchers have discovered that the structure, shape, and production technique of CNTs imposed a significant impact on their electrochemical performance when employed as LIB materials. ,, For example, CNTs prepared by chemical vapor deposition displayed good specific capacity at low current density, but they suffered from high irreversible capacity and severe voltage hysteresis. , Furthermore, various studies have shown that etching, ball milling, and oxidation treatment could improve the reversible capacity of CNTs. For example, Gao et al .…”
Section: Introductionmentioning
confidence: 99%